Morphological and molecular characterization of common bean landraces and cultivars from the Caribbean - Durán, L.A.; Blair, Matthew W.; Giraldo Zapata, Martha C.; Macchiavelli, Raúl E.; Prophete, E; Nin, JC; Beaver, James S. (Wiley, 2005)
Little information is available regarding the relationship of Caribbean bean landraces with the Andean and Mesoamerican gene pools of common bean (Phaseolus vulgaris L.) While small-seeded Mesoamerican black beans are prevalent in parts of the Caribbean, many of the regionally preferred red mottled and medium-to-large-seeded bean landraces found there are postulated to belong to the Andean gene pool. To test this hypothesis, we analyzed the morphological characteristics, phenological traits, phaseolin status, and random amplified polymorphic DNA (RAPD) banding patterns of 54 red mottled or large-seeded bean landraces and cultivars from the Caribbean (16 from the Dominican Republic, 14 from Haiti, 1 from Jamaica and 23 from Puerto Rico) compared with 11 Andean bean lines from other regions. To estimate phylogenetic relationships among the lines, distances were calculated and dendrograms constructed for morphological and/or phenological and molecular characteristics by the complete clustering method. The landraces were grouped into two clusters morphologically: one with Mesoamerican characteristics, which included all the red mottled lines from Haiti and three landraces from the Dominican Republic collected near the Haitian border and the other with Andean characteristics, which included all the lines from Puerto Rico and the remaining lines from the Dominican Republic. RAPD and phaseolin polymorphisms identified three groups, one corresponding to the genotypes with Mesoamerican morphologies, one to those with Andean morphologies, and another that had Andean phenotypes but proximity to the Mesoamerican group, suggesting possible introgression between the gene pools. Phaseolin variability agreed with other molecular and morphological data allowing the assignment of genotypes to a Mesoamerican or Andean gene pool. Knowledge of this variability may provide useful information concerning the potential value of Caribbean landraces to Andean bean breeding programs.